Isolation and identification of microorganisms from total petroleum hydrocarbon-contaminated soil sites - Jiji, J. (2023)
Crude petroleum oil is a rich source of hazardous materials that can cause soil and water pollution which can be treated by natural biodegradation processes. The aim of this study was to isolate and identify native oil degrading microorganisms from a petroleum-contaminated soil. The study was conducted at Changanassery, Kottayam district in Kerala, India. A total of six bacterial and four fungal strains were isolated from the samples. Isolated bacterial strains were Pseudomonas aeruginosa, Bacillus subtilis, Pseudomonas spp, Bacillus spp and Staphylococcus aureus. Fungal isolates were identified as Aspergillus niger, Aspergillus spp, Aspergillus flavus, Pencillium spp. It was observed that these organisms were able to utilize and degrade crude oil constituents.